2020
DOI: 10.1093/nutrit/nuaa028
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium levels in relation to rates of preterm birth: a systematic review and meta-analysis of ecological, observational, and interventional studies

Abstract: Context Experimental studies suggest that magnesium levels in pregnant women may affect the length of gestation, as magnesium affects the activity of smooth muscle in the uterus. Little is known about the association between magnesium levels or supplementation and the rate of preterm birth. Objective The aim of this systematic review was to summarize the data on magnesium soil levels and preterm birth rates from ecological, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
(77 reference statements)
0
14
0
Order By: Relevance
“…In the present study, the results indirectly showed that Mg substantially influenced the length of a pregnancy. Preterm labor is associated with uterine muscle cell hyper-reactivity [ 26 , 76 ] or endothelial dysfunction [ 77 ]. Kovo et al [ 78 ] confirmed the significant anti-inflammatory effect of Mg in an experimental study on placentas, and selected cotyledons were cannulated.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the results indirectly showed that Mg substantially influenced the length of a pregnancy. Preterm labor is associated with uterine muscle cell hyper-reactivity [ 26 , 76 ] or endothelial dysfunction [ 77 ]. Kovo et al [ 78 ] confirmed the significant anti-inflammatory effect of Mg in an experimental study on placentas, and selected cotyledons were cannulated.…”
Section: Discussionmentioning
confidence: 99%
“…This was also supported by the study of non-pregnant adults who received oral Mg supplements (16) . Moreover, higher MMI would maintain pregnancy and prolong gestation because higher maternal serum Mg levels were associated with the activity of uterine smooth muscle (preterm birth group: 0•93 mmol/L v. control group: 1•12 mmol/L, p < 0•01) (11,12) and may be associated with a decreased incidence of childhood wheezing in offspring. These may have protected the offspring from childhood asthma and wheezing.…”
Section: Discussionmentioning
confidence: 99%
“…Mg is a common factor involved in the function of enzymes and acts as a cofactor in over 600 enzymatic reactions (11) . Mg is important during pregnancy because it also affects uterine smooth muscle activity (12) , which could affect the pregnancy and offspring; additionally, it exerts various benefits, including anti-inflammatory and antioxidant effects (13) . Several studies have reported that adequate maternal magnesium intake (MMI) reduces preterm births, foetal growth restriction, small-for-gestational-age births and pre-eclampsia (14) .…”
mentioning
confidence: 99%
“…One study found that the risk of orofacial clefts was significantly lower in mothers with dietary intakes of 376-404 mg/day of magnesium (OR 0.4) [81]. One ecological study across the U.S. found a strong inverse correlation between magnesium levels in soil and the rates of preterm birth (r = −0.68; p < 0.001) [99].…”
Section: Comparison With Commercial Prenatalsmentioning
confidence: 99%
“…A more recent metanalysis of six RCT's with 3068 pregnant women found that magnesium supplementation significantly reduced the rate of preterm birth (RR = 0.58, CI = 0.35-0.96) [99].…”
Section: Comparison With Commercial Prenatalsmentioning
confidence: 99%